When Teacher Enthusiasm Is Authentic or Inauthentic: Lesson Profiles of Teacher Enthusiasm and Relations to Students' Emotions - Melanie M. Keller; Eva S. Becker; Anne C. Frenzel; Jamie L. Taxer (SAGE Publishing, 2018)
It was recently proposed that teacher enthusiasm encompasses an experienced component as well as a behaviorally displayed component. Aiming to validate this proposition, the present study utilized lesson diaries to explore patterns of teacher-reported experienced enthusiasm and student-reported enthusiastic teaching behaviors and to investigate whether those patterns were related to students' enjoyment and boredom. Findings imply that the two enthusiasm components do not always co-occur. Four lesson profiles were identified: (1) experienced enthusiasm and enthusiastic teaching coinciding at a high level, (2) teachers reporting high levels of experienced enthusiasm but not being perceived as enthusiastic, (3) teachers being perceived as enthusiastic but not reporting high levels of experienced enthusiasm, and (4) low levels of experienced enthusiasm and enthusiastic teaching. The first pattern was superior to the other profiles regarding students' emotions. Study findings are discussed with respect to teachers' emotional well-being and teaching effectiveness.